Study on Implementation of Lean Six Sigma in Hospital Auxiliary Ship Block Construction Process - Muhammad Rizki Kurniawan; Rr. Rochmoeljati (Department of Naval Architecture - Diponegoro University, 2022)
During the pandemic, transportation is needed to support the evacuation of patients through waterways; therefore, PT PAL Indonesia (Persero) has created a Hospital Auxiliary Ship project. In building a quality Hospital Auxiliary ship project, productivity is needed so the project can be completed properly. However, there are problems with the punctuality of completing the ship block construction with a total lead time of 19200 minutes and found the block quality is not up to standards like Surface Porosity, Former Stopper, Arc Strike, and Low Bead defects that require a rework process and cause long cycle times. This study aims to reduce the lead time value and minimize waste or activities that are not value-added using the lean six sigma method with stages (DMAIC). From the results of the study, it was found that the identification of the Process Activity Mapping (PAM) design, which resulted in the highest waste rating, namely 16.94% defect, with CTQ-4, lean six sigma value of 3.055 sigma and DPMO value of 59917 which was included in the excellent category for the industry average. The factors causing the problem were identified with Pareto diagrams and causal diagrams to determine the dominant type of defect and the causes of wastage of defects; there are four factors, namely material, human, machine, and environment. Recommendations for the improvement of waste are through material inspection, operator training, reworking defective blocks, and minimizing non-value-added activities. With the design of process activity mapping (PAM) and value stream mapping, the efficiency of ship block construction can increase from 67.81% to 74.06%.